Marble hall murders eaudiobook - Horowitz, Anthony (Magpie Murders, 2025)
Murder links past and present once again in this mind-boggling metafictional mystery from Anthony Horowitz featuring detective Atticus Pünd and editor Susan Ryeland, stars of the New York Times bestsellers Magpie Murders and Moonflower Murders. Editor Susan Ryeland has left her Greek island, her hotel and her Greek boyfriend, Andreas, in search of a new life back in England. Freelancing for a London publisher, she's given the last job she wants: working on an Atticus Pünd continuation novel called Pünd's Last Case. Worse still, she knows the new writer. Eliot Crace is the troubled grandson of legendary children's author Miriam Crace who died twenty years ago. Eliot is convinced she was murdered—by poison. To her surprise, Susan enjoys reading the manuscript which is set in the South of France and revolves around the mysterious death of Lady Margaret Chalfont, days before she was about to change her will. But when it is revealed that Lady Margaret was also poisoned, alarm bells begin to ring. The more Susan reads, the clearer it becomes that Eliot has deliberately concealed clues about his grandmother's death inside the book. Desperately, Susan tries to prevent Eliot from putting himself in harm's way—but his behaviour is becoming increasingly erratic. Another murder follows . . . and suddenly Susan finds herself to be the number one suspect. Once again, the real and the fictional worlds have become dangerously entangled. And if Susan doesn't solve the mystery of Pünd's Last Case, she could well be its next victim.